Nutritional composition of selected commercial biscuits in Malaysia - Norhayati, M.K.; Mohd Fairulnizal, M.N.; Zaiton, A.; Wan Syuriahti, W.Z.; Rusidah, S.; Aswir, A.R.; Ang., J.L.; Mohd Naeem, M.N.; Suraiami, M.; Mohd Azerulazree, J.; Vimala, B. (Universiti Kebangsaan Malaysia, 2015)
The objective of this study was to determine the nutrient composition of selected commercial biscuits in Malaysia. A total of six brands from each type of biscuit (chocolate chip, corn, cracker with sugar, vegetable flavoured cracker, cream filled, oatmeal, shortbread and fully coated chocolate wafer) and five brands of wholemeal crackers were sampled from local supermarkets in the Klang Valley. The total energy content in commercial biscuits was ranging from 453.30 to 499.25 kcal/100 g. Carbohydrate was the major macronutrient in commercial biscuits ranging from 56.86 to 66.07 g/100 g. The highest protein content was found in the wholemeal crackers (9.92 g/100 g) and the lowest protein content was found in the cream filled biscuits (5.65 g/100 g). Fat content lay in the range of 16.89 to 25.75 g/100 g. The major minerals detected in biscuits were sodium, followed by calcium and magnesium. The vitamin content in A and E of the biscuits examined was almost comparable. Small quantities of trans fatty acids were detected in all biscuits in the range of 0.02 to 0.68 g/100 g. These findings indicate that Malaysian commercial biscuits are a good source of carbohydrate (34.12-39.64 g per serving), calcium (26.09-384.67 g per serving), magnesium (10.42-37.24 g per serving) and contain low proportion of trans fatty acids (0.01-0.41 g per serving).